2011
DOI: 10.1055/s-0030-1268437
|View full text |Cite
|
Sign up to set email alerts
|

Warm-Up Affects Diurnal Variation in Power Output

Abstract: The purpose of this study was to examine whether time of day variations in power output can be accounted for by the diurnal fluctuations existent in body temperature. 8 recreationally trained males (29.8±5.2 yrs; 178.3±5.2 cm; 80.3±6.5 kg) were assessed on 4 occasions following a: (a) control warm-up at 8.00 am; (b) control warm-up at 4.00 pm; (c) extended warm-up at 8.00 am; and, (d) extended warm-up at 4.00 pm. The control warm-up consisted of dynamic exercises and practice jumps. The extended warm-up incorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…This research group found that passive heating somewhat improved morning muscle strength but still it did not reach the neuromuscular performance level found in the afternoon. Likewise, active warm-up, despite raising the morning aural body temperature and increasing muscle force and power output levels, did not increase motor performance to the levels found in the afternoon [4], [16], [17]. These studies suggest that body temperature is one of the most critical components of the circadian rhythm effects on motor performance.…”
Section: Introductionmentioning
confidence: 62%
“…This research group found that passive heating somewhat improved morning muscle strength but still it did not reach the neuromuscular performance level found in the afternoon. Likewise, active warm-up, despite raising the morning aural body temperature and increasing muscle force and power output levels, did not increase motor performance to the levels found in the afternoon [4], [16], [17]. These studies suggest that body temperature is one of the most critical components of the circadian rhythm effects on motor performance.…”
Section: Introductionmentioning
confidence: 62%
“…Similarly, a warm environment improves diurnal variation in the morning 68) . However, a rise in body temperature due to warming is not always effective in improving diurnal variation [69][70][71][72][73] . In a study in which warming was applied in the morning to increase body temperature to the same level as evening body temperature, did not produce any change in swimming performance 72) .…”
Section: Temporal Effectiveness Of Exercise Training and Sportsmentioning
confidence: 99%
“…Likewise, oral temperature is time-of-day dependent, with high afternoon values and morning nadirs (Deschenes et al 1998;Hammouda et al 2011Hammouda et al , 2012. This diurnal variation in oral temperature could partially explain time-of-day fluctuations in short-term maximal performance (Martin et al 1999;Taylor et al 2011). However, previous studies showed that these diurnal variations in performance could be modified by the time of day at which specific training was performed (Hill et al 1988(Hill et al , 1989Sedliak et al 2007Sedliak et al , 2008Sedliak et al , 2009.…”
Section: Introductionmentioning
confidence: 99%